Healthcare advisor as a new majorin response to the needs of the healthcare system - Rezner, Anna; Rezner, Witold (Polish Journal of Public Health, 2012)
Significant information needs of healthcare system customers which cannot be fully satisfied using conventional resources of the increasingly loaded healthcare system constitute a demand for services provided by healthcare advisors. These professionals would primarily supply information helpful and sometimes necessary in optimizing access to services provided by growing in complexity public and private healthcare systems.Healthcare advisors could also play many additional professional roles based on practical knowledge concerning products and services in healthcare and direct advisor-client relationship.Depending on the candidates’ initial level of education, tuition could be realized in course of bachelor and master programmes or during postgraduate studies. Bearing in mind experiences of other sectors, healthcare advisor education could open perspectives for interesting and attractive career, and the services would help to improve healthcare system by facilitating information flow.